Prefabricating marginality: long-term housing impacts of displacement in post-disaster Montserrat. Issue 2 (4th May 2021) - Hooper, Michael
ABSTRACT: This paper investigates the long-term housing impacts of displacement and explores how these vary across disaster-affected populations. The Caribbean island of Montserrat, an overseas territory of the United Kingdom, provides an excellent setting for examining this relatively understudied topic. Following the eruption of the Soufrière Hills volcano, beginning in 1995, most Montserrat residents were displaced and the island's south was declared an exclusion zone. The paper draws on interviews with 89 randomly selected residents, including displacees and non-displacees, and with 10 Montserratian and United Kingdom officials charged with responding to post-disaster needs. The paper seeks to understand variation in long-term housing conditions with a focus on the impact of housing type. The results show that interviewees living in housing built for, rather than by, displacees had significantly lower housing satisfaction scores, with residents of prefabricated houses reporting the lowest scores. Interviewees argued that the top-down provision of these houses was problematic due to limited local input and use of materials poorly suited to local conditions and traditions. The paper concludes by situating the findings in the context of the literature on post-disaster housing and by arguing for increased attention to how such housing is provided in terms of both process and materials.